The effects of functional training and stationary cycling on respiratory function of elderly with Parkinson disease: a pilot study - Raíssa Almeida da Silveira; Karen Valadares Trippo; Gabriel Pereira Duarte; Mansueto Gomes Neto; Jamary Oliveira Filho; Daniel Dominguez Ferraz (Editora Champagnat, 2018)
Abstract Introduction: Respiratory function changes in patients with Parkinson's disease (PD) contribute to aspiration pneumonia, the main cause of mortality in PD population. Objective: To compare the effects of functional training and cycle exercise in respiratory function of elderly with PD. Methods: Twenty participants were randomised into two groups. Experimental group (EG) (n = 10) performed cycle exercise and control group (CG) (n = 10) was trained with functional training. A blinded researcher evaluated maximal inspiratory pressure (MIP), maximal expiratory pressure (MEP), thoracoabdominal amplitude, forced vital capacity (FVC) and forced expiratory volume in the first second (FEV1) before and after interventions. Results: Both groups did not improve significantly respiratory function. Only CG improved significantly FVC (p = 0.01). No differences were found between groups. Conclusion: 8-week exercise programs are not able to improve the respiratory function of elderly in 2 to 3 PD Hoehn & Yahr stage. Both functional training and cycle exercise do not to improve respiratory function in elderly with PD.